Crystal Imperfection Modulation Engineering for Functionalization of Wide Band Gap Semiconductor Radiation Detector. (29th December 2017) - Ji, Xu; Chen, Liang; Xu, Mengxuan; Dong, Mei; Yan, Kun; Cheng, Shuang; Kong, Xueqian; Wang, Tongyao; Liu, Jiandang; Gu, Bingchuan; Wang, Huanhua; Liu, Zhiyong; et al.
Abstract: Controllable and repeatable crystal imperfection modulation engineering (CIME) is important for the development of semiconductor science and technology. However, for wide band gap semiconductors (WBGSs), there still lacks universal and reliable CIME. Here, based on the general idea of chemical composition complete expression design, a well‐designed, repeatable, and feasible CIME for ZnO is introduced, making free modulation of carrier in WBGS become possible. Briefly, this extraordinary CIME is dominated by two innovative procedures: an electrochemical doping and a strong oxidizing atmosphere annealing. The proposed CIME is a repeatable and universal carrier modulation project, which holds technological promise for various WBGS‐based semiconductor devices. Benefiting from this CIME, an α particle detector which operating at a high electric field of 10 7 V cm −1 can be fabricated successfully. Abstract : A universal and creative electrochemical assistant crystal imperfection modulation engineering (CIME) is exploited and designed to modulate the carrier concentration of one prototypical wide band gap compound semiconductor (WBGCS), ZnO, to an ultralow level. Based on this material, a high‐performance radiation detector is fabricated. This excellent WBGCS‐CIME offers significant reference for all compound semiconductor materials.